Polyarchy: The Transition from Democratic Passivity to Democratic Participation A Critique on the Translation Book Polyarchy: Participation and Opposition - Mohammad Zohdi Goharpour; Fatemeh Sayadi; Rasoul Afzali (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
For more than 40 years, Robert Dahl’s theory of polyarchy democracy has been considered by scholars as one of the most effective, robust, and enlightening forms of contemporary revisionist democratic theory. The English version of this book was published in 1971 and its translation was published in 2018. Polyarchy is defined as a set of institutional arrangements that allow for public opposition and inclusive participation in politics. The central assumption of the sign in this book, which involves a linear process, is that when hegemonic systems and competitive dictatorships move toward multiculturalism, opportunities for effective participation and questioning increase. Therefore, the number of individuals, groups, and interests whose policy priorities are considered increases. In this article, an attempt is made to examine the intellectual background and studies of Robert Dahl over two decades (1970-1950) and to identify the roots of the development of his theory of polyarchy democracy, presented in the form of an independent book, in his earlier works.